The role of health self-efficacy, health assertiveness, and risk perception on the relationship between vaccination knowledge and vaccination intention - Nazori, Mohd Nazir Mohd (2022)
Current childhood vaccination coverage has achieved herd immunity. However, a concerning trend of vaccine-preventable disease incidence and vaccine hesitancy demand the need for better health promotion interventions. Health self-efficacy, health assertiveness (assert to be informed and assert opinion), and risk perception (perceived likelihood and perceived severity) were proposed as the tailoring basis for the relationship between vaccination knowledge and vaccination intention. This study has two phases. Phase I study aims to: (i) To develop risk perception instrument in the context of childhood vaccination, and (ii) Establish validity and reliability of vaccination knowledge, health self-efficacy, health assertiveness, risk perception, and vaccination intention instruments. Phase II study aims to discover: (i) Level of vaccination knowledge, health self-efficacy, health assertiveness, risk perception, and vaccination intention among pregnant mothers; (ii) Differences in vaccination knowledge and vaccination intention according to education and income level; (iii) Relationships between health self-efficacy, health assertiveness, and risk perception; and (iv) The mediating effect of health self-efficacy, health assertiveness, and risk perception on the relationship between vaccination knowledge and vaccination intention. Each construct was measured using questionnaire in a cross-sectional design. The questionnaire was validated during Phase 1 on 108 pregnant mothers and Phase 2 objectives were addressed using 924 pregnant mothers attending primary and rural health clinic in the district of Gombak, Klang, Hulu Langat, and Petaling. Respondents were sampled using multi-stage random sampling with those involved in Phase 1 was excluded from Phase 2 study. For Phase 1 study, the instruments were analysed for content validity, construct validity using exploratory and confirmatory factor analysis, and reliability using Cronbach’s alpha. For Phase 2 study, data were analysed in SPSS version 27 using descriptive statistics, Welch’s ANOVA, and Pearson’s correlation, and in AMOS version 27 using structural equation modelling. Results of Phase 1 study reported a reduction in the number of items across measured constructs with the final list of items showing satisfactory validity and reliability. Results of Phase 2 study reveal high level of vaccination knowledge, health self-efficacy, health assertiveness, risk perception, and vaccination intention. There is significant difference in vaccination knowledge and vaccination intention between education and income level (p < 0.01). Health self-efficacy show moderate positive relationship with health assertiveness (p < 0.01), whereas both constructs showed weak positive relationship with risk perception (p < 0.01). Only risk perception shows full mediating effect on vaccination knowledge and vaccination intention (p < 0.05), whereas health self-efficacy and health assertiveness are not a significant mediator. The mediation model showed satisfactory fit. As health assertiveness and health self-efficacy is moderately related, mothers should be encouraged to learn about vaccination knowledge. Vaccination knowledge will impact positively on vaccination intention only if high risk perception was formed as a result of the knowledge. Therefore, the focus of health education intervention should be on formation of risk perception related to vaccination. Novelty of this research is in encouraging a shift of focus from information-deficit model to psychological characteristics in understanding vaccination knowledge and vaccination-related outcomes amongst pregnant mothers.Additionally, healthcare professional will be informed on possible ways to tailor their approach and target of their intervention. An empowering approach that builds upon health self-efficacy and health assertiveness should be considered during intervention and development of policy.